2008
DOI: 10.1037/a0014179
|View full text |Cite
|
Sign up to set email alerts
|

The developmental origins of a disposition toward empathy: Genetic and environmental contributions.

Abstract: The authors investigated the development of a disposition toward empathy and its genetic and environmental origins. Young twins' (N = 409 pairs) cognitive (hypothesis testing) and affective (empathic concern) empathy and prosocial behavior in response to simulated pain by mothers and examiners were observed at multiple time points. Children's mean level of empathy and prosociality increased from 14 to 36 months. Positive concurrent and longitudinal correlations indicated that empathy was a relatively stable di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
358
2
12

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(399 citation statements)
references
References 60 publications
27
358
2
12
Order By: Relevance
“…Our analysis suggests that these parameters can be collapsed into a single dimension, because the participants who were most likely to sacrifice those who had a lower payoff than themselves were also the most likely to sacrifice for those who had a higher payoff, and for those who had (or hadn't) shown bad intentions. This supports other work indicating that a common underlying factor (in part) influences social preferences (Eisenberg et al, 2002;Lewis & Bates, 2011b;Knafo et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…Our analysis suggests that these parameters can be collapsed into a single dimension, because the participants who were most likely to sacrifice those who had a lower payoff than themselves were also the most likely to sacrifice for those who had a higher payoff, and for those who had (or hadn't) shown bad intentions. This supports other work indicating that a common underlying factor (in part) influences social preferences (Eisenberg et al, 2002;Lewis & Bates, 2011b;Knafo et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…At the same time, these normative changes are constrained by inter-individual variations, which are associated with various psychological, biological, and social differences. For example, research has shown that there is a genetic effect on children's empathy at 24 and 36 months of age (Knafo, Zahn-Waxler, Van Hulle, Robinson, & Rhee, 2008).…”
Section: A Developmental Perspective On Moral Emotionsmentioning
confidence: 99%
“…We focused on the correlation between WM of BM and empathy, an essential aspect of normal social functioning, which has been extensively studied in the last decades from developmental, social, clinical, and neuroscience perspectives (e.g., Baron-Cohen & Wheelwright, 2004;Batson et al, 1997;Blakemore, 2008;Decety & Jackson, 2004;Knafo et al, 2008;Shamay-Tsoory, 2011). Empathy, broadly defined, refers to the cognitive as well as the emotional reactions of an individual to the observed experiences of other individuals (Shamay-Tsoory, 2011).…”
Section: Introductionmentioning
confidence: 99%